Perovskite device physics - Ummu Sumaiyah Eliase (2016)
This is an undergraduate final year project report focusing on perovskite devices and the physics behind them. This includes a brief summary of some existing perovskite devices, with a special focus on the applications resulting from the hybrid organic-inorganic organo metal halide perovskite. In the summary, I will touch on aspects such as the device fabrication, device structure and operating principle, the interesting physics for further research, and possibly a comparison with non-perovskite based counterparts. The experiment done involves a study of the mobility and light emission characteristics of OFETs utilising a methylammonium lead iodide (MAPbI3) semiconductor through varying the solvent and temperature. It was found that carrier mobility does appear to affect light emission.